2017
DOI: 10.18869/acadpub.jbrms.4.1.17
|View full text |Cite
|
Sign up to set email alerts
|

E-test antibiotic susceptibility of E.coli strains isolated from hospital acquired infections of Imam Khomeini hospital, Ilam, Iran

Abstract: Introduction: Escherichia coli (E.coli) as a main cause of both nosocomial and communityacquired infections in humans have a relative potential to develop resistance. Nowadays, most infections caused by ESBL-producing E.coli (ESBLEC) had mostly been described as nosocomial acquired or nursing home related. In this study, we employed E-test assay to detect antibiotic resistance of E.coli strains and determine MIC of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…coli and P. aeruginosa bacteria were included in gramnegative bacteria which are known to be resistant to various antibiotics. This condition is supported by the ability of E. coli to produce extended -spectrum β-Lactamases enzymes (Extended Spectrum β-Lactamases/ESBL) which can degrade certain antibiotics (βlactam class) ( (Farhat et al, 2009 ;Bimanand et al, 2017)) and can form capsules (Khan et al, 2015), while P. aeruginosa can form biofilms (Alhazmi, 2015). Based on Podschun & Ullmann (1998) and Khan et al (2015), the common triggers of malignancy from these gram-negative bacteria are the presence of endotoxin (toxin which is an integral part of cell walls of gram-negative bacteria) and adhesin (extracellular matrix and plasma protein deposits used to attach to biomaterials).…”
Section: Resultsmentioning
confidence: 99%
“…coli and P. aeruginosa bacteria were included in gramnegative bacteria which are known to be resistant to various antibiotics. This condition is supported by the ability of E. coli to produce extended -spectrum β-Lactamases enzymes (Extended Spectrum β-Lactamases/ESBL) which can degrade certain antibiotics (βlactam class) ( (Farhat et al, 2009 ;Bimanand et al, 2017)) and can form capsules (Khan et al, 2015), while P. aeruginosa can form biofilms (Alhazmi, 2015). Based on Podschun & Ullmann (1998) and Khan et al (2015), the common triggers of malignancy from these gram-negative bacteria are the presence of endotoxin (toxin which is an integral part of cell walls of gram-negative bacteria) and adhesin (extracellular matrix and plasma protein deposits used to attach to biomaterials).…”
Section: Resultsmentioning
confidence: 99%
“…The anti-malarial drugs artemisinin and its derivatives (artesunate, dihydroartemisinin, artemether, and arteether) have been clinically used to treat malaria ( 18 , 19 , 30 ). Artesunate was also revealed to increase the susceptibility of various β-lactam antibiotics against E. coli by increasing antibiotics accumulation via inhibiting the efflux pump system, AcrAB-TolC, an essential and significant multi-drug efflux pump system within E. coli ( 31 , 32 ). Results showed that oxacillin had the greatest MIC, while ciprofloxacin had the lowest MIC, supported by those reported by CLSI ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial susceptibility of the clinical isolates and the standard strain to standard synthetic chemical antibiotics was assessed using rapid e-tests 4,5,7 , Briefly, the isolates were inoculated onto separate plates containing Mueller-Hinton agar and standard e-test plastic strips were infused with each antibiotic and incubated with the isolates at 37°C overnight to develop zones and ellipses. The interaction of the ellipse was taken as the minimum inhibitory concentration (MIC), whereas the zone indicated the susceptibility of the antibiotic to the bacterium.…”
Section: Antimicrobial Susceptibility Testsmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a Gramnegative motile bacterium that is a major cause of community-acquired, and hospital-borne nosocomial infections 1,2 . The major concern about nosocomial infections with P. aeruginosa is that > 10% of infections are caused by multidrugresistant species 1,3,4 that arise through antibiotic abuse. Pseudomonas is only one among many bacterial species that have become resistant to multiple antibiotics, and the most resistant strain is P. aeruginosa 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation